Could eggshell membrane be an adjuvant for recombinant Hepatitis B vaccine?: A preliminary investigation - Parker Elijah Joshua; Charity Chinyere Ilo; Uzochukwu Gospel Ukachukwu; Damian Chukwu Odimegwu; Rita Onyekachukwu Asomadu; Timothy Prince Chidike Ezeorba (SpringerOpen, 2023)
Abstract Background Despite the invasiveness of the Hepatitis B infection, its vaccines are only formulated with FDA-approved alum-based adjuvants, which poorly elicit a lasting immune response, hence the need for a more effective adjuvant system. This study evaluated the immunogenicity and toxicity of eggshell membranes (ESM) when administered as an adjuvant for the recombinant HBV vaccine (rHBsAg) in albino mice. Differential white blood cell analysis, as well as the titer measurement of Immunoglobulin G, subclass G1 and G2a on indirect ELISA, was performed to measure the immune-modulatory potentials of ESM. Moreover, analysis of the liver marker enzyme (AST and ALT) and body/liver weights was performed to ascertain the toxicity level of ESM. Finally, Immuno-informatic analysis was used to investigate the immune-modulatory potential of individual member proteins of ESM. Results Our results showed a significant improvement in the experimental group's lymphocyte count after boost-dose administration compared to the controls, whereas there was no significant change in the granulocyte population. Furthermore, the formulations (ESM-rHBsAg) significantly improved IgG and IgG1 titers after each successive immunization. Body/liver weight and liver function showed ESM non-toxic to mice. The immunoinformatic analysis discovered ovalbumin, lysozyme-C, and UFM-1 as the member proteins of ESM with immune-modulatory activities of activating antigen-presenting cells (APC). Conclusion This study has provided a clue into the potential valorization of eggshell membranes and their peptides as an adjuvant for vaccines such as HBV. We recommend more in-depth molecular analysis to support our findings as well as foster real-life application.